Analysis Of Lempuyang Commodity Marketing Channels In Sukoharjo Regency - Risma Gayatri, Rahajeng; Setiyani, Rahmawati; Sepfrian, Bimoseno (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The agricultural sector in Indonesia includes various subsectors, one of which is medicinal plants. Sukoharjo Regency is one of the areas in Central Java Province that has high potential for cultivating medicinal plants, one of which is lempuyang. Lempuyang is used by some farmers and the community by selling it directly to consumers or processing it into processed products. Lempuyang cultivation has quite promising value, however obstacles in farming are also experienced by lempuyang farmers in Sukoharjo Regency, namely the relatively low income of farmers. This research aims to determine the marketing channels for lempuyang commodities in Sukoharjo Regency. This research uses descriptive analysis methods. Sampling of farmers used a probability sampling system and sample determination was carried out using the proportional sampling method using Lemeshow calculations with the results of 96 respondents. Sampling of producers, traders and consumers uses a purposive method with certain criteria. Based on research that has been carried out, it can be seen that there are four marketing channels for lempuyang in Sukoharjo Regency, namely channels I: Farmers-Traders-Consumers, channels II: Farmers-Collectors¬-Traders-Consumers, channels III: Farmers-Collectors¬-Semi-finished materials industry- Traders-Consumers, and channels IV: Farmers-Collectors¬-Fixed materials industry-Traders-Consumers. It is hoped that this research will enable farmers to achieve marketing efficiency and find out which channels provide the highest profits.